Equations of state for amorphous and crystalline nickel by means of molecular dynamics method - Ozgen, Soner; Songur, Levent; Kara, Izzet (Tubitak Scientific & Technological Research Council Turkey, 2012)
There are few theoretical studies on the equation of state (EOS) for amorphous materials while much work has been carried out for crystalline systems. In this study, the EOSs for both crystal-and amorphous-structured nickel are obtained by using an anisotropic molecular dynamics method based on the Voter-Chen formalism of embedded atom method. In order to achieve the EOSs, polynomial curve fitting method has been applied to the data obtained from molecular dynamics simulations carried assuming isothermal and isobaric conditions. Isothermal bulk modulus and their pressure derivatives for both amorphous and crystal structures have also been calculated. The results are compared with the values obtained from well-known Vinet and Davydov EOSs.
Keywords: Equation of state; molecular dynamics simulation; amorphous structures; embedded atom method